Application of Picture and Picture with PowerPoint Media to Improve Student Learning Outcomes on Human Digestion Food in The SD Negeri 54 Banda Aceh - Zubaidah Zubaidah; Muhibuddin Muhibuddin; Cut Nurmaliah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2015)
The study, entitled “Application of  Picture and Picture with  power point  media to improve student learning outcomes on human Digestion Food in the Elementary School 54 Banda Aceh’ was caried out on August to September 2013 at SDN 54 Banda Aceh. This study aimed to determine the increase student learning outcomes in V class  through the application of Picture and Picture with  Power Point  media to Improve Student learning outcomes on human Digestion Food in the Elementary School 54 Banda Aceh’. The methode used in this study is experimental with Pretest-postest control group design. Data were obtained from the administration of pretest and posttest at the end of the lesson. Analysis of the data using the t test. The statistical results showed that the value of the t-test was 4,21 then t count t-table of 1.645. The conclusion of this study was application of picture and picture with power point media was increased student learning outcomes than using convensional method